Implementation of Technology-Enhanced Learning Media Based on Technological Pedagogical and Content Knowledge (TPACK) to Improve Student Engagement in PAI Learning - Mir'atul Maimanah; Masfufah Masfufah; Amir Bandar Abdul Majid (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to determine the implementation of TPACK-based learning media, to determine the increase in student learning activity, and to determine the supporting and inhibiting factors for the implementation of TPACK-based learning media in increasing student activity in Islamic Religious Education subjects at SMA Wahid Hasyim 2 Taman Sidoarjo. This type of research is qualitative research with an inductive descriptive approach. Data collection techniques use observation, interviews, and documentation. This study is based on the conditions of SMA Wahid Hasyim 2 Taman Sidoarjo. Duringn the learning process, some students tend to be less active and unproductive in the Islamic Religious Education learning process. The results of this study are that the implementation of TPACK-based learning media in Islamic Religious Education subjects at SMA Wahid Hasyim 2 Taman Sidoarjo went well. In its implementation, Islamic Religious Education teachers at SMA Wahid Hasyim 2 Taman Sidoarjo have involved TPACK in the learning process. This can be seen from the learning planning that Islamic Religious Education teachers have made in the teaching module, Students feel more interested in learning Islamic Religious Education because the methods used are not boring and there are always new things that can be learned through technology. The research results conclude that the implementation of TPACK-based learning media in Islamic Religious Education learning can increase student activity. It can be seen from the activity of students who were initially less active in learning, which showed an increase in active learning after implementing TPACK-based learning media.